Plant Growth-Promoting Microbe Mediated Uptake of Essential Nutrients (Fe, P, K) for Crop Stress Management: Microbe–Soil–Plant Continuum - Pattnaik, Swati; Mohapatra, Balaram; Gupta, Abhishek (Frontiers in Agronomy, 2021)
The indiscriminate and intensive use of agrochemicals in developing nations to enhance crop productivity has posed an alarming threat to soil quality, fertility, biodiversity, food safety, agricultural sustainability, and groundwater quality, thus critically affecting planetary health and food productivity. Additionally, both abiotic and biotic stresses and developmental disorders, i.e., disease susceptibility, hormonal imbalance, and nutritional deficiency, are the major constraints on crop productivity. In this context, the use of soil–plant associated microbiomes “phytomicrobiome,” especially rhizospheric microbiota, in combination with agronomic practices (nutrient, water, and resource management, as integrated management options: INM/IPM/IWM) is the most promising alternative for managing soil health and crop productivity. The global recognition of plant/soil-associated microbiome has generated substantial investment of public and private bodies to grow microbe-based food products. However, understanding the molecular, genetic, physiological, and ecological aspects of phytomicrobiome toward sustainable agriculture would require broad attention along with associated environmental/physico-chemical control points. The underpinning mechanisms of plant–microbe interactions are of immense significance for strategizing host selection (single culture/consortia) and its field application. Taxa such as Rhizobium, Pseudomonas, Alcaligenes, Burkholderia, Sphingomonas, Stenotrophomonas, Arthrobacter, Bacillus, and Rhodococcus have emerged as promising plant growth-promoting (PGP) candidates with diverse beneficial traits, such as, producing phyto-hormones, volatile organics, antibiotics for disease suppression, N2-fixation, Fe uptake, and extracellular enzymes, but several physico-chemical constraints/extremities limit the field application (on-site) of such microbes. Hence, a detailed overview on genomic, physiological, metabolic, cellular, and ecological aspects is necessitated. Thorough insights into nutrient acquisition (especially limiting nutrients like Fe and P) during abiotic stress are still under-studied, so the use OMICS, robust bioinformatics pipeline/tools, might greatly revolutionize the field of PGP microbial ecology (complex plant–microbe interactions) for application in agricultural sustainability, nutritional security, and food safety. This review focusses on critical aspects of mechanisms of Fe and P transport-uptake (nutrient acquisition) by various PGP microbes, and their metabolism, genetics, and physiology relevant for managing stress and better crop production.